Fashion: Malaysian Muslim women perspective - Jan, Muhammad Tahir; Abdullah, Kalthom (2015)
This paper introduces an in-depth discussion of the various interpretations of what fashion is, and the items considered as part and parcel of fashion. Generally fashion is seen as an object of beautification for women, yet it brings new meanings to their lives when it enhances self- confidence, facilitates the communication of their self-identity and self- esteem, besides depicting their culture or society. A discussion of the purposes of fashion items such as shoes, makeup/cosmetics, apparel and accessories is discussed. A section of the paper is devoted to a discussion of the Muslim scarves (hijab), as the focus of this paper is on the perception of what fashion means to Muslim women. This paper serves as a fruitful insight into the minds of the Muslim women consumers and provides impetus for the marketing of fashion-related items to serve this segment of the market. A conceptual framework developed for this study would be the initial attempt at developing a more comprehensive study into the related moderating and mediating variables that has an effect on fashion. This study also suggests that future researchers may consider testing the proposed model empirically, not only in Malaysia but also in other countries. Lastly, a promising attempt would be to test for invariance among different countries on the same model.